EVALUATION OF THE RELATIONSHIP BETWEEN SPRAY LIQUID PRESSURE AND MACHINE SPEED USING THREE TYPES OF NOZZLES ON A BOOM SPRAYER - G. Tihanov; G. Hristova; P. Veleva (IRAQI JOURNAL OF AGRICULTURAL SCIENCES, 2025)
This study investigates the efficiency of three types of flat fan nozzles (blue, red, and brown) when operating with a boom sprayer under low-volume spraying conditions in the Gorno Botevo village area of Central Bulgaria. The experiment evaluated the sprayer’s operational speed and working pressure across eight working regimes, focusing on the impact of speed and nozzle type on application performance. Statistical analyses, including univariate ANOVA and correlation analysis, revealed significant differences in performance among the nozzles. The blue, red, and brown nozzles achieved optimal performance at 8.5 km/h, 12 km/h, and 16 km/h, respectively, while maintaining the recommended pressure range of 4–5 bar. Predictive nonlinear models were developed, explaining 42.2% to 75.4% of the variation in nozzle pressure as influenced by speed. These models provide practical guidance for optimizing sprayer operation, enhancing pesticide application efficiency, and minimizing resource waste. This study contributes to advancing precision agricultural practices by offering actionable insights into the interplay between speed, pressure, and nozzle performance under field conditions.